Primary health care organization in municipalities of São Paulo, Brazil: a model of care aligned with the Brazilian Unified National Health System's guidelines - Castanheira, Elen Rose Lodeiro [UNESP]; Duarte, Ligia Schiavon; Viana, Monica Martins de Oliveira; Nunes, Luceime Olivia [UNESP]; Zarili, Thais Fernanda Tortorelli; Mendonca, Carolina Siqueira [UNESP]; Sanine, Patricia Rodrigues [UNESP] (Cadernos Saude Publica, 2024)
This study analyzes the main organization patterns used by primary health care (PHC) services in municipal networks and evaluates them according to indicators of local management -administration interface. Evaluative research analyzed 461 municipalities in Sito Paulo, Brazil, that participated in the Primary Care Services Quality Assessment Survey (QualiAB) in 2017/2018, classified according to the organizational arrangements composition of 2,472 PHC services. Eight indicators of local management and administration were selected to evaluate the identified patterns. Results indicate two groups of municipalities: homogeneous, with services presenting the same arrangement (43.6%); and heterogeneous, with different arrangements (56.4%). These were subdivided into seven patterns that ranged from homogeneous-traditional, homogeneous-Family Health Strategy, homogeneous-mixed, and different combinations in the heterogeneous group. All indicators showed significant differences between groups (p < 0.001), especially the homogeneoustraditional group, which presented an organizational pattern far from the desired model of a comprehensive and problem-solving PHC. Those integrated with family health units (FHU) and basic health units with community health workers and/or family health teams (BHU/FHU) showed a pattern closer to a comprehensive model - with planning and evaluation actions committed to the local reality and qualification of care. Implementation of federal and state policies are essential for defining the PHC health care model adopted by municipalities.
Keywords: Primary Health Care; Healthcare Models; Health Services Evaluation; Organization and Administration